"90 seconds to midnight": climate change, planetary collapse and the "mystification" of environmental crime - Walters, Reece (Demystifying power, crime and social harm, 2023)
As the introduction to this book attests (Scott and Sim, this volume), Steven Box’s confronting scholarship laid bare the hypocrisy and corruption of state and corporate power; radically challenged and championed the sociology of deviance through his critical analyses of the criminalisation process with an astute inculcation of discourses in science, law and political economy.